Outage Performance Analysis of Non-Orthogonal Multiple Access with Time-Switching Energy Harvesting - Van, Hoang Thien; Nguyen, Hoang-Sy; Nguyen, Thanh-Sang; Huynh, Van Van; Nguyen, Thanh-Long; Sevcik, Lukas; Voznak, Miroslav (Elektronika ir Elektrotechnika, 2019)
In recent years, although non-orthogonal multiple access (NOMA) has shown its potentials thanks to its ability to enhance the performance of future wireless communication networks, a number of issues emerge related to the improvement of NOMA systems. In this work, we consider a half-duplex (HD) relaying cooperative NOMA network using decode-and-forward (DF) transmission mode with energy harvesting (EH) capacity, where we assume the NOMA destination (D) is able to receive two data symbols in two continuous time slots which leads to the higher transmission rate than traditional relaying networks. To analyse EH, we deploy time-switching (TS) architecture to comprehensively study the optimal transmission time and outage performance at D. In particular, we are going to obtain closed-form expressions for outage probability (OP) with optimal TS ratio for both data symbols with both exact and approximate forms. The given simulation results show that the placement of the relay (R) plays an important role in the system performance.